Roselle and Red Ginger: A Potential Combination of Medicinal Plants for Hypertension Therapy - Yunas, Ranum Wanudya; Rahmawati, Siti Irma; Saputri, Fadlina Chany; Bayu, Asep; Chianese, Giuseppina; Putra, Masteria Yunovilsa (UI Scholars Hub, 2024)
Hypertension is a prevalent cardiovascular condition that significantly increases the risk of heart disease and stroke. Effective management is essential to prevent severe complications. Roselle (Hibiscus sabdariffa L.) and red ginger (Zingiber officinale var. rubrum) are two medicinal plants known for their antihypertensive properties. Roselle contains bioactive compounds such as anthocyanins that exhibit vasodilatory and angiotensin-converting enzyme (ACE) inhibition, while red ginger is rich in gingerols and shogaols, which possess anti-inflammatory and vasodilatory properties. The complementary mechanisms of action of these two plants, including ACE inhibition, antioxidant activity, and modulation of vascular tone, result in a more pronounced antihypertensive effect when used together. By targeting multiple pathways, the combination allows for more effective blood pressure control, which could lead to improved patient outcomes. The purpose of this study is to provide a detailed review of the evidence supporting the use of roselle and red ginger in combination as a potential therapeutic approach for hypertension. This review aims to identify gaps in the existing research and suggest directions for future studies. Understanding the synergistic effects of these plants can help in developing more effective herbal therapies that leverage their combined benefits. Further research is needed to confirm these findings through more in-depth preclinical and clinical studies. Investigations should focus on optimizing dosages, understanding long-term safety, and establishing standardized protocols for combination therapy. This review serves as a foundation for future research and encourages the integration of traditional herbal medicine into modern hypertensive management strategies, promoting a holistic approach to cardiovascular health.